Silicon Mitigates the Effects of Boron Deficiency and Toxicity in Plants - Kadyampakeni, Davie (2023)
Boron (B) content in tropical soils is generally low. It limits agricultural production, and the difference between the appropriate and toxic concentrations for foliar application is tenuous. In this scenario of nutritional disorder due to B deficiency or toxicity, applying the beneficial element silicon (Si) has shown promise in plants grown in tropical climates. The benefits of Si can alleviate the deleterious effects of nutritional disorders by B and are associated with the chemical characteristics of the beneficial element in the soil and roots. Silicon helps maintain the development of the root system and water relations and can form complexes with B, limiting its absorption in toxicity. In shoots, Si can increase the production of several compounds, such as carbohydrates, proteins, indole-acetic acids, and phenols, which can alleviate the deleterious effects of B-nutritional disorder. In addition, Si can increase the enzymatic and non-enzymatic antioxidant systems. At the reproductive phase, Si can contribute to flower formation and the production and viability of pollen grains of B-deficient plants. In this chapter, we seek to summarize the main action mechanisms of the B and Si interaction in the development of tropical plants; the synergistic and combined effects on the soil solution and the root system; and the impacts on biomass production, shoot development, and the development of reproductive organs of plants cultivated in tropical climates under B nutritional disorder.